The Morphological Structures of the Topic of Patience in the Holy Qur’an and their Implications (Islamic Sciences Journal, 2023)
This research deals with the pure fluctuations of the substance (saber) patience in the holy quran and its implications, and the study is a semantic- morphological study. it also shows what happens to this article of pure fluctuations between the actual and the nominal, and the act came from it and its three sections: past, present and command.         As for the nominal fluctuations, they came from: derived names such as the source, the name of the agent and the formulas of exaggeration, as well as the masculine and feminine, the singular, the dual and the plural.
Keywords: Section, condition, disagreement, doctrinal issues, practical examples.